PROBLEMATIKA IMPLEMENTASI QOWAID AL-LUGHAH DALAM MEMBACA KITAB KUNING DI MADRASAH TA'HILIYAH IBRAHIMY - Aisyatul Hanun; Almannah Wassalwa (LP2M Universitas Ibrahimy, 2017)
Qowaid al-lughah is a science that much needed in learning Tutoring Reading Kitab, appropriate with real condition ofÂ failure learning to read kitab it resulted by any matter. There are, the teacher emphasize to attention of Qowaid al-Lughah for memorizing nadzam and material being studied. Qowaid al-Lughah function as a tool to read Kitab with correct harokat which less attention. So, we need for adjustments between ability of Qowaid al-Lughah with assemblingÂ reading skill of students. Authority students ofÂ Qowaid al-Lughah (Nahwu-Sharraf) does not necessarily ensure students are able to read kitab classics.